Quantification of experimental venous thrombus resolution by longitudinal nanogold-enhanced micro-computed tomography - Grover, Steven P. (Thromb Res, 2015)
INTRODUCTION: The assessment of thrombus size following treatments directed at preventing thrombosis or enhancing its resolution has generally relied on physical or histological methods. This cross-sectional design imposes the need for increased numbers of animals for experiments. Micro-computed tomography (microCT) has been used to detect the presence of venous thrombus in experimental models but has yet to be used in a quantitative manner. In this study, we investigate the use of contrast-enhanced microCT for the longitudinal assessment of experimental venous thrombus resolution. MATERIALS AND METHODS: Thrombi induced by stenosis of the inferior vena cava in mice were imaged by contrast-enhanced microCT at 1, 7 and 14 days post-induction (n = 18). Thrombus volumes were determined longitudinally by segmentation and 3D volume reconstruction of microCT scans and by standard end-point histological analysis at day 14. An additional group of thrombi were analysed solely by histology at 1, 7 and 14 days post-induction (n = 15). RESULTS: IVC resident thrombus was readily detectable by contrast-enhanced microCT. MicroCT-derived measurements of thrombus volume correlated well with time-matched histological analyses (ICC = 0.75, P < 0.01). Thrombus volumes measured by microCT were significantly greater than those derived from histological analysis (P < 0.001). Intra- and inter-observer analyses were highly correlated (ICC = 0.99 and 0.91 respectively, P < 0.0001). Further histological analysis revealed noticeable levels of contrast agent extravasation into the thrombus that was associated with the presence of neovascular channels, macrophages and intracellular iron deposits. CONCLUSION: Contrast-enhanced microCT represents a reliable and reproducible method for the longitudinal assessment of venous thrombus resolution providing powerful paired data.